Dynamics of Post-Defense Gift-Giving Among Students: Between Appreciation, Trends, and Financial Pressure - Natalia, Devitri; Idrus, Idham Irwansyah; Ahmad, M. Ridwan Said; Najamuddin, Najamuddin (SIGn Journal of Social Science, 2025)
Post-defense gift-giving practices in higher education have undergone a fundamental transformation. This practice has shifted from a mere emotional expression to a complex and dilemmatic sociological phenomenon. This study aims to critique the hegemony of digital trends and psychological pressure manifested as the Fear of Missing Out (FoMO). Such pressure transforms the tradition of appreciation into a ritual of simulacra that obscures the essence of academic celebration. This research employs a qualitative design with a phenomenological approach. Its objective is to explore the intersubjective experiences of 11 students selected through purposive sampling. Data were analyzed in depth using a synthesis of critical theories by Baudrillard and Mauss. The research results successfully deconstruct three key findings. First, the fundamental motive for gift-giving has shifted from a drive of sincere affection to a strategic effort of self-construal under the control of social media algorithms. Second, the gift object is no longer valued for its utility but operates as a sign value. This reproduces social stratification and class hierarchy through the consumption of global brands. Third, the creation of a reciprocity paradox. The illusion of group solidarity is inherently mechanical and comes at a high cost: economic alienation and the pressure of a morally binding debt of gratitude. This study concludes that student social interaction has been co-opted by market logic. Therefore, there is an urgent need to strengthen symbolic and financial literacy to liberate students from the trap of consumerism disguised as social support. Additionally, a more substantial, inclusive, and humanizing redefinition of academic solidarity is required.